Structure and physiology of developing neuromuscular synapses in culture - Takahashi, T (J Neurosci, 1987)
The structure and function of developing neuromuscular synapses in culture have been investigated. We used neuromuscular junctions formed by coculturing dissociated muscle cells and dissociated neurons obtained from Xenopus embryos. After recording nerve-evoked endplate potentials (e.p.p.s) and spontaneously occurring miniature endplate potentials (m.e.p.p.s) from a given junction, the same specimen was investigated for electron-microscopic histology. We surveyed almost the total area of the junctional region by making serial sections. Even in preparations cocultured for only a short time (4–11 hr), both e.p.p.s and m.e.p.p.s could be obtained. The junctional region of these early synapses revealed a simple structure. The presynaptic terminals contained smooth-surfaced clear vesicles, but there were no presynaptic specializations such as active zones. The width of the synaptic cleft was variable, with predominance of narrow regions (10–30 nm), and there was no basal lamina inside the cleft. When the coculture time was 1 d or longer, the junctional area started to show structural features resembling a mature neuromuscular synapse. In the presynaptic terminal there were active zones, consisting of the presynaptic density and an accumulation of vesicles near the density. In many junctions, the postsynaptic membrane showed densities and thickenings, with a widened synaptic cleft, that contained basal lamina. It is known that growth cones, prior to making neuromuscular junctions, can release the transmitter substance with a very long latency if stimulated repetitively. In contrast, e.p.p.s with short latencies can be evoked by single stimuli soon after the growth cones attach to muscle cells. However, our data did not reveal any structural changes to account for such functional changes.(ABSTRACT TRUNCATED AT 250 WORDS)